포스트모더니즘 이후 인체 조각에 나타나는 비정형 신체 이미지 연구 - 강덕봉; Kang Duck Bong (기초조형학연구, 2018)
본 연구는 ‘비정형(Formless)’ 개념을 바탕으로 포스트모더니즘 이후 인체 조각에 나타나는 비정형 신체 이미지를 연구한 논문이다. 서구의 형이상학 속에서 ‘정형’의 예술론 세계를 드러내야 했던 억압된 신체에서, 사회적 담론을 반영하는 창작의 주체로 ‘형상전이(Transfiguration)’한 비정형 신체에 대한 고찰로 논지를 이끈다. 작품 해석의 근거가 되는 조르주 바타유의 비정형 개념을 알아보고, 이브-알랭 부아와 로잘린드 E. 크라우스의 「비정형: 사용자안내서」에 나오는 비정형의 4가지 작동 기제들을 바탕으로 포스트모더니즘 이후 인체 조각에 나타나는 비정형신체 이미지를 탐구하는데 그 주된 목적이 있다. 일반적으로 ‘비정형’은 고의적인 왜곡이나 변형으로 인해, 그것의 형태와 형식이 정해지지 않은 것을 의미한다. 미술사에서 ‘비정형’은 20세기 초 조르주 바타유가 초현실주의의 미학을 정의하기 위해서 제시한 개념이다. 그것은 정형화된 시각언어를 거부하고, 사물의 형태를 해체하여 예술의 상징적 내용과 형식적 질서의 전복을 목적으로 한다. ‘비정형’은 모더니즘의 ‘주체성’과 ‘순수성’의 퇴조 이후, ‘모호함’과 ‘불투명성’의 양상이 드러나는 포스트모더니즘이 등장하면서 다시 주목받게 되었다. 그리고 1996년 파리의 퐁피두센터에서 열린 <비정형: 사용자 가이드>전의 전시도록에서 부아와 크라우스에 의해 ‘저급 유물론’, ‘수평성’, ‘펄스’, ‘엔트로피’라는 주요 표제어를 바탕으로 다양한 현대미술의 동향과 흐름을 분석하는 새로운 패러다임으로 확장되었다. 이에 본 연구자는 현대 인체 조각에서 해체와 파편화를 통해 비형식주의 또는 비재현적으로 등장하는 신체 이미지와 비정형의 연관성에 주목하였다. 그중에서 ‘저급유물론’을 바탕으로 개인적 자아와 사회적 정체성을 드러내는 키키 스미스의 저급한 신체와 인체 조각들을 수직축으로부터 수평적 구도로 연출해 ‘시각의 수평성’을 초래한 안토니 곰리의 작품을 고찰하였다. 그리고 ‘펄스’적 요소를 바탕으로 시각영역에 신체적 감각을 도입해 ‘시간성’과 ‘육체성’을 회복한 스텔락의 융합된 신체와 기존의 의미체계를 전복시키는 ‘엔트로피’ 전략을 통해 인간의 욕망과 금기에 대해 다시 생각하게 하는 채프먼 형제의 변형된 신체를 분석하였다. 이를 근거로 현대 인체 조각에서 비정형 신체 이미지가 변화하는 사회적 시각을 반영하고, 인간 자의식을 드러내는 예술적 매체로 그 영역을 확장하고 있음을 살펴봄으로써, 현대 인체 조각에서 신체 이미지의 해석 가능성을 넓히는 발판으로 모색하고자 한다. This paper examines the formless body images presented in figurative sculptures since postmodernism based on the concept of formlessness. The paper is primarily informed by a series of observations on formless bodies that have been transfigured to subjects of creativity representing prevailing social discourses from oppressed bodies used to express ‘formulaic’ art amid Western Metaphysics. The main purpose is to understand the concept of formlessness as defined by Georges Bataille that provides the basis for interpretation of art works and to explore the formless body images demonstrated in figurative sculptures since the emergence of postmodernism, based on the four elements of formlessness outlined in 「 Formless: A User’s Guide」 by Yve-Alain Bois and Rosalind E. Krauss. Generally, ‘formlessness’ means having no definite form or shape due to intentional distortion or transformation. A study of art history suggests that ‘formlessness’ is a concept introduced by Georges Bataille in the early 20th century to define the surrealist art. Its aim is to reject formulaic visual languages and deconstruct the form of an object so that they can destroy symbolic meanings and the order of arts. ‘Formlessness’ was brought into spotlight again as modernism defined by subjectivity and purity gave way to postmodernism characterized by ambiguity and opaqueness. And it was the catalogue of an exhibition called 「 Formless: A User’s Guide」 held in the Centre Pompidou in Paris that the formlessness evolved into a new paradigm that analyzes a wide array of trends and movements of modern arts based on key words such as Base Materialism, Horizontality, Pulse, and Entropy by Yve-Alain Bois and Rosalind E. Krauss. This has brought the attention of the author of this paper to a link between the formlessness and the non-formalistic or non-representational body images presented in modern figurative sculptures through deconstruction and fragmentation. The study particularly focused on observations on the visceral representations of human bodies by Kiki Smith that depict personal self-awareness and social identity based on Base Materialism and works by Antony Gormley who created Visual Horizontality by forming a horizontal line with figurative sculptures representing verticality. The study also analyzes the integrated bodies created by Stelarc who restored the elements of time and body by introducing bodily senses into visual areas based on Pulse element and the transformed bodies created by the Chapman brothers who relied on Entropy strategy designed to destroy the framework of conventional meanings to make one rethink about desire and taboo. Based on the observations described above, the study intends to explore formless body images presented in modern figurative sculptures that reflect changing social perspectives and evolve into artistic media used to reveal human self-consciousness, which can allow more room for possible interpretations of body images presented in modern figurative sculptures.